LEXICAL COMPLEXITY IN THE INTRODUCTIONS OF UNDERGRADUATE STUDENTS’ RESEARCH ARTICLES - Ratna Dewi (Universitas Muhammadiyah Makassar, 2017)
Lexical complexity refers to the various different words employed in the introductions of the undergraduate students’ research articles. The implementation of lexical complexity describes the writers’ overall development of lexical complexity use in the target language. This study aims to find out the employment of lexical complexity in the introductions of undergraduate students’ research articles. It utilized a quantitative design through corpus based analysis.The corpus studied consisted of 134 introductions of undergraduate students’ research articles. The data were analyzed using Web-based Lexical Complexity Analyzer. Then to decide the level of complexity applied in the students’ articles, the results were compared to the lexical complexity of Chinese learners’ oral narratives. The findings show that lexical density, lexical sophistication, and lexical variation are high except for verb variation, noun variation, adjective variation, adverb variation and modifier variation (cf. Lu, 2010, 2012; Ai Lu, 2013). It is expected that this article could provide information about the lexical complexity which is needed to be improved in the undergraduate students’ research articles.